"She's been involved in everything as far as I can see": Supporting the active participation of people with intellectual disability in community groups. Issue Volume 40:Issue1(2015) (2nd January 2015) - Craig, Diane; Bigby, Christine
Abstract: Background The social processes that operate in community groups need to be better understood if people with intellectual disability are to be included in such groups. This study aimed to identify the nature and impact of the group processes on the active participation of people with intellectual disability. Method Extensive field notes were taken during 2 years of participant observation whereby 5 people with a moderate level of impairment were supported to participate as individuals in community groups for periods of 5 to 10 months. Analysis used a critical realist approach. Results Active participation was influenced by the interaction of 5 key social processes: leadership response, characteristics of the participants with intellectual disability, access to expertise, the presence of an integrating activity, and dealing with the difference dilemma. Conclusions By revealing these processes, the study identified a number of interventions and ways of approaching community groups that have the potential to increase the extent to which people with moderate levels of impairment become active participants.